Alarm scent-marking during predatory attempts in the Cabrera vole (Microtus cabrerae Thomas, 1906) - Pereira Gomes, Luis Alexandre (2013)
The alarm pheromones often released by animals under stressful situations seem to elicit behavioral changes in conspecifics, which in the appropriate context can be viewed as anti-predatory responses. However, the releasing of alarm pheromones associated with predatory events has not been demonstrated in mammals. In the current study with wild-caught Cabrera voles, we carried out experiments in the laboratory and in the field to assess the release of alarm pheromones in scent-marks during simulated predatory events and disclose their effects on conspecifics. We first conducted an assay wherein voles where let to scent-mark a clean substrate in the absence of disturbance (control) and under the simulation of predatory events. Contrarily to the control, no fecal boli were released and the area marked with urine was significantly larger during the predatory simulation. In a subsequent assay, we assessed the voles' preference between urine-marks released under predatory simulation and in control conditions. Voles showed a significant preference by control substrates. Finally, a third assay was carried out in the vole's habitat wherein the individual activity was monitored by radio-tracking before and after placement of urine-marks obtained during the conditions described above. The vole's activity was only reduced near the urine-marks released during the simulated predatory events. The results suggest that: (1) during predatory attempts, Cabrera voles release an alarm pheromone in their urine-marks; (2) the putative alarm pheromone reduces the voles' activity in the surroundings of the marked area; (3) the putative alarm pheromone persists in the field affecting conspecifics' activity for several days.